Altered risk-aversion and risk-seeking behavior in bipolar disorder. - Chandler, R; Wakeley, J; Goodwin, G; Rogers, R (2009)
BACKGROUND: Bipolar disorder (BD) is associated with high-risk behaviors, such as gambling and impulsivity. However, little is known about the psychological factors that influence these behaviors or their significance for the development of the disorder. In this study, we investigated the effects of highlighting rewards versus highlighting punishments in the risky decision-making of euthymic individuals with bipolar disorder. METHODS: Twenty euthymic, medication-free men and women with previously undiagnosed bipolar II or bipolar disorder not otherwise specified and 20 age- and IQ-matched healthy men and women completed a computerized risky decision-making task in which mathematically equivalent dilemmas were presented in terms of opportunities to gain rewards ("positively-framed") or to avoid suffering losses ("negatively-framed"). The dependent measures were the proportion of risk-seeking choices (and deliberation times) when making decisions in positively versus negatively framed dilemmas. RESULTS: As expected, healthy control participants made more risky-seeking choices in response to the negatively framed dilemmas compared with the positively framed dilemmas. However, this effect was significantly attenuated in BD participants who also took significantly longer to make risk-averse responses to the positively framed dilemmas. The BD participants overestimated the number of bad outcomes arising out of positively framed dilemmas. CONCLUSIONS: These data demonstrate that risky choice in BD is associated with reduced sensitivity to emotional contexts that highlight rewards or punishments, possibly reflecting altered valuations of prospective gains and losses associated with behavioral options.